Method for preparing low-carbon common-density structural concrete by using artificial aggregate

By replacing natural sand and gravel in ordinary structural concrete as specific artificial aggregates, and preparing spherical granular aggregates in combination with autoclaving and sintering processes, the performance problems of concrete when using regenerated aggregates and artificial aggregates are solved, and the effect of reducing cement consumption and water consumption and improving concrete performance and durability is achieved.

CN119899001APending Publication Date: 2025-04-29BEIJING UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411929525.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

When using recycled aggregates and artificial aggregates, existing concretes have problems with ease, mechanical properties and durability, and the increase in cement usage leads to higher costs and increased carbon emissions, limiting the application of artificial aggregates in structural concrete.

Method used

By replacing natural sand and gravel into specific artificial aggregates in medium volumes of ordinary structural concrete, combining spherical granular aggregates prepared by autoclaving and sintering processes, adjusting the concrete mix ratio, reducing cement and water consumption, and improving aggregate grading and fluidity.

Benefits of technology

It is achieved without changing the concrete density, improve the construction performance of concrete, reduce shrinkage and cracking, improve durability, and reduce costs and carbon emissions by reducing cement usage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899001A_ABST
    Figure CN119899001A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing low-carbon common-density structural concrete by using artificial aggregates. Several types of special artificial aggregates are used for replacing natural gravel in common structural concrete in an equal-volume manner, a small amount of artificial aggregates are doped, the density of the concrete is not remarkably changed, it is guaranteed that the concrete belongs to the category of common structural concrete, and the fluidity of the concrete is improved by fully utilizing grading of the artificial aggregates and spherical particles; the internal curing effect is provided by utilizing the water absorption-water release effect of the artificial aggregate, and conditions are provided for adjusting the mixing ratio of the concrete (reducing the cement consumption and the water consumption). The dry apparent density prepared by the method is similar to that of common structural concrete, and meanwhile, the problem that a cementing material needs to be additionally added to provide better working performance due to poor grain shape and gradation of natural aggregate is solved; the risks of large shrinkage and more cracks caused by too large use amount of a cementing material can be effectively reduced; the cost can be reduced by reducing the use amount of cement, and the consumption of natural gravel resources is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials. Background Art

[0002] As a non-renewable natural resource, sand and gravel should be used economically. We need to find new recycled materials to replace natural sand and gravel in concrete to meet the requirements of sustainable development of human society.

[0003] At present, there are two more recognized solutions to the problem of shortage of natural sand and gravel. One is to replace natural sand and gravel with recycled aggregates from construction waste, and the other is to replace natural sand and gravel with artificial aggregates (such as sintered expanded clay, etc.).

[0004] The development and utilization of recycled aggregates from construction waste is to promote the sustainable development of concrete from the perspective of circular economy. However, due to the presence of uncleanly stripped old mortar on the surface of the aggregate, the recycled aggregate has high water absorption and poor interface in the transition zone, which causes several problems in the workability, mechanical properties and durability of concrete. Therefore, when using recycled aggregates to prepare concrete, the amount of cement is often increased to make up for the above-mentioned deficiencies. However, cement, as a raw material with high energy consumption and high carbon emissions, is the most important factor affecting the carbon footprint of concrete. Therefore, the increase in cement consumption will increase the cost of recycled aggregate concrete and increase carbon emissions, which ultimately leads to the current lack of widespread application of recycled aggregate concrete.

[0005] Sintered expanded clay is a kind of artificial aggregate that is well known to people. It is characterized by light weight and good stability. It has advantages in thermal insulation, fire resistance and durability. Lightweight aggregate concrete also mostly uses sintered expanded clay as aggregate.

[0006] In recent years, artificial aggregates produced by autoclaving have also appeared (CN201910322988.6 A kind of artificial fine aggregate silicate clay sand and its preparation method, CN202210711324.0 A method for preparing high-strength artificial aggregate using molybdenum tailings, CN202310840392.1 Autoclaved silicate functional aggregate to prepare low-carbon, lightweight and high-strength concrete with a density of 1800-1900kg / m3 and its method). Compared with expanded clay, it is characterized by high density and high cylinder pressure strength. Since the autoclaving temperature is 180-200℃, the energy consumption is low, and it can absorb a variety of siliceous and calcareous solid wastes, showing a high cost performance and development and application prospects.

[0007] Artificial aggregates such as expanded clay are mainly used to prepare lightweight aggregate concrete, which is a special type of concrete. Because its price is significantly higher than ordinary concrete, and its elastic modulus is low and its construction is difficult, it is rarely used in structural concrete.

[0008] From the perspective of concrete performance, how to improve the construction performance of concrete, how to reduce shrinkage and cracking, and how to improve the durability of concrete have always been the main direction of efforts to develop high-performance concrete; from the perspective of green and low-carbon, the carbon footprint of concrete, the contribution from cement accounts for about 80%, the contribution from raw materials and the transportation of finished products accounts for about 8%-9%, and the contribution from production and other aspects is about 10%. Therefore, how to reduce the amount of cement while meeting the performance of concrete is the main direction of efforts for green and low-carbon concrete.

[0009] In the past few decades, the improvement of the performance of ordinary structural concrete has mainly relied on the progress of admixture technology and additive technology to achieve the purpose of reducing cement dosage and improving concrete performance. However, there are few methods to achieve green and low-carbon concrete preparation by adding some artificial aggregates with certain specific technical requirements to natural sand and gravel, improving aggregate grading and composition, and providing internal maintenance.

[0010] Among artificial aggregates, sintered ceramsite and aggregates prepared by autoclaving are suitable for structural concrete, but most of them are used to prepare lightweight concrete (dry apparent density less than 1950kg / m 3 ), typical patents include: CN201611192312.2 A lightweight high-strength concrete suitable for pumping construction and its construction method and CN202011144614.9 A lightweight high-strength concrete and its preparation method and application, both coarse aggregate and fine aggregate are sintered coarse ceramsite (5-20mm) and sintered ceramic sand (0-5mm). And CN201911171098.6 LC50-LC80 lightweight high-strength silicate ceramsite concrete mix design method, and CN201911171080.6 lightweight high-strength silicate ceramsite concrete, all coarse aggregates are autoclaved silicate ceramsite with a particle size of 5-16mm, and the prepared concrete dry apparent density is less than 1950kg / m 3 .

[0011] At present, the application of artificial lightweight aggregate is mainly to prepare lightweight aggregate concrete, and most of them do not take the preparation of structural concrete of normal density as a technical goal. Lightweight aggregate concrete is a special concrete. Due to its huge differences in economic cost, physical and mechanical properties, etc. from ordinary structural concrete, its application in my country is relatively small, especially as structural concrete, which accounts for less than one ten-thousandth of the total concrete. Therefore, lightweight aggregate concrete is not a mainstream concrete product. At present, the most used concrete is C20-C80 ordinary structural concrete (wet density is 2300-2500kg / m 3). Common structural concrete is mainly composed of six components: cement, auxiliary cementitious materials (admixtures), water, coarse aggregate (stone), fine aggregate (sand), and admixtures. Among them, coarse aggregate is mostly natural pebbles and crushed stones, and fine aggregate is mostly river sand and machine-made sand. At present, ordinary structural concrete generally does not contain artificial aggregates. Summary of the invention

[0012] The present invention replaces the natural sand and gravel in ordinary structural concrete with certain types of special artificial aggregates in equal volumes. The addition of a small amount of artificial aggregates does not significantly change the density of the concrete, ensuring that the concrete belongs to the category of ordinary structural concrete. The gradation and spherical particles of the artificial aggregates are fully utilized to improve the fluidity of the concrete, and the water absorption-release effect of the artificial aggregates is used to provide internal curing, which provides conditions for adjusting the concrete mix ratio (reducing the amount of cement and water). This method can prepare a dry apparent density similar to that of ordinary structural concrete, and at the same time solve the problem that due to the poor particle shape and gradation of natural aggregates, additional cementitious materials (cement and mineral admixtures are collectively referred to as cementitious materials) are needed to provide better working performance for the concrete mixture; it can effectively reduce the technical risks of large shrinkage and multiple cracks caused by excessive use of cementitious materials; it can reduce costs by reducing the amount of cement, reduce the consumption of natural sand and gravel resources, and alleviate the problems of price increases caused by shortages of natural sand aggregates.

[0013] (1) A method for preparing green low-carbon ordinary structural concrete using human aggregate, characterized in that: on the basis of the conventional mix ratio of C20-C80 ordinary structural concrete, specific artificial coarse aggregate and fine aggregate accounting for 5%-25% of the total volume of aggregate are added according to a certain method, and at the same time, the cement dosage is reduced by 10-150kg / m 3 , water consumption is reduced by 5-50kg / m 3 , and appropriately adjust the sand ratio, and fill in the insufficient volume with admixtures to obtain a green and low-carbon ordinary structural concrete.

[0014] (2) The conventional mix ratio of C20-C80 ordinary structural concrete is the mix ratio obtained in accordance with the current industry standard JGJ55 "Ordinary Concrete Mix Ratio Design Code" or the mix ratio obtained by professionals based on experience. The total amount of cementitious materials in the mix ratio is usually 250kg / m 3 -700kg / m 3 In addition to ordinary Portland cement as a necessary component, other components of cementitious materials may include but are not limited to fly ash, slag powder and other mineral admixtures. The proportion of mineral admixtures generally does not exceed 50%. The specific proportion can be adjusted according to actual needs. The water-cement ratio in the mix ratio is usually 0.25-0.55. The specific value is adjusted according to the actual concrete strength. The amount of sand in the mix ratio is usually 550kg / m 3 -950kg / m 3The specific amount is adjusted according to the actual sand parameters and concrete strength. The amount of crushed stone in the mix ratio is usually 900kg / m 3 -1200kg / m 3 , the specific amount is adjusted according to the actual crushed stone parameters and concrete strength;

[0015] The specific artificial coarse aggregate and fine aggregate are mainly made of solid waste as raw materials, produced by autoclaving or sintering, with high sphericity, fine aggregate (autoclaving) of 1.18mm-5mm and coarse aggregate (autoclaving or sintering) of 5mm-25mm, and the apparent density of the aggregate is 1700-2500kg / m 3 , the average cylinder pressure strength is not less than 8MPa, and the water absorption rate in 1 hour is 5-20%;

[0016] The specific artificial coarse aggregate and fine aggregate are added in a proportion of 5% to 30% of the total volume of the aggregate. The maximum proportion of addition is related to the apparent density of the artificial aggregate: when the apparent density of the artificial aggregate is too large (1950-2500kg / m 3 ) The maximum proportion of the admixture can reach 30% of the total volume of the aggregate. When the density of the artificial aggregate is relatively small (1700-1950kg / m 3 ) The maximum incorporation ratio can reach 20% of the total aggregate volume;

[0017] The mixing method is as follows: both the coarse and fine aggregates are autoclaved aggregates, or the fine aggregates are autoclaved aggregates, the coarse aggregates are sintered ceramsite or a mixture of sintered ceramsite and autoclaved aggregates, wherein the volume ratio of the artificial coarse aggregate to the total volume of the artificial coarse and fine aggregates is not greater than 50%. The artificial aggregates replace the natural sand and gravel in equal volumes.

[0018] There are two ways to add artificial aggregate: 1) Pre-saturate with water for at least 24 hours in advance. When adding, remove the floating water on the surface of the aggregate to make it close to the saturated surface dry state, and then add it to the mixer in the usual way; 2) Add it to the mixer in a dry state, first add part or all of the additional water, stir with the artificial aggregate for at least 20 seconds, and add other materials in the usual way.

[0019] The appropriate adjustment of the sand ratio is to increase or decrease the volume sand ratio of the mixed aggregate by 2%-5%;

[0020] The insufficient volume is supplemented by admixtures. After reducing the amount of cement and water, the concrete volume is less than 1 cubic meter. The part should be added with admixtures according to the insufficient volume. Preferably, a corresponding volume of fly ash is added.

[0021] The green low-carbon ordinary structural concrete has a mixture wet density of 2200-2500kg / m 3, the cement dosage is reduced by 5%-30%, the 28d compressive strength of the concrete is more than 95% of the original mix strength, and the 72h shrinkage is reduced by more than 30% compared with the original mix.

[0022] 3. Technical effects:

[0023] (1) Compared with other existing technologies, the present invention partially replaces natural aggregate with autoclaved aggregate and sintered ceramsite, so as to prepare concrete with economic cost and physical and mechanical properties similar to those of ordinary structural concrete. It does not belong to special concrete and has a market prospect of a large number of applications.

[0024] (2) By utilizing the characteristics of artificial aggregates, such as high density, high sphericity, and controllable gradation, the particle shape and gradation of the aggregate system can be improved and optimized, thereby significantly improving the workability of concrete. The improvement in concrete workability creates favorable conditions for optimizing the concrete mix ratio and reducing water consumption. Since water consumption is reduced, the amount of cement can be further reduced, which can not only make up for the cost increase caused by replacing natural sand and gravel aggregates with artificial aggregates, but can even reduce the overall cost of concrete when the amount of cement is reduced significantly.

[0025] (3) Artificial aggregates have large porosity and certain water storage and release capabilities. They can provide additional curing water for the core concrete that is not connected to the outside of the concrete, delay the self-drying process of the concrete and make the hydration of the core concrete more complete. The internal curing effect of this artificial aggregate can significantly reduce the shrinkage of concrete, promote the later strength development of concrete, improve the durability of concrete, and create conditions for increasing the use of a larger proportion of admixtures and reducing the amount of cement.

[0026] (4) The present invention will realize the widespread use of artificial aggregates in ordinary structural concrete, and it is estimated that 100-200 million tons of artificial aggregates can be used in concrete every year. Artificial aggregates, whether autoclaved aggregates or sintered ceramsite, can be prepared in large quantities using solid waste, and the solid waste utilization rate exceeds 95%.

[0027] To sum up, the method of preparing ordinary density structural concrete with autoclaved aggregate and sintered expanded clay innovatively proposed in the present invention not only consumes a large amount of solid waste in total and saves natural sand and gravel resources, but also optimizes concrete performance, reduces cement usage, reduces shrinkage cracking, and improves concrete durability. It can be said to be a technology that profoundly changes the way solid waste is utilized and significantly improves the comprehensive performance of concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is the cumulative pass rate of sand and gravel.

[0029] Figure 2 This is the technical route of the present invention.

[0030] Figure 3 is the slump of the C60 test group.

[0031] Figure 4 It is a summary of the compressive strength and wet density of each example mix. DETAILED DESCRIPTION

[0032] The raw materials used are Jinyu brand P.O42.5 cement, Grade I fly ash and S95 slag powder that meet national standards, basalt machine-made sand, basalt machine-made gravel, as well as fine autoclaved aggregate, coarse autoclaved aggregate and sintered ceramsite. The autoclaved aggregate used in the test is produced by Zhejiang Zhongjin Environmental Protection Co., Ltd., and the sintered ceramsite is produced by Anhui Dongchen New Materials Technology Co., Ltd., but it is not limited to these companies as long as the performance meets the requirements of Table 1. The specific fine autoclaved aggregate and coarse autoclaved aggregate can be fine silicate autoclaved aggregate and coarse silicate autoclaved aggregate respectively. In the example, the fine autoclaved aggregate and the fine silicate autoclaved aggregate are the same substance. In the example, the coarse autoclaved aggregate and the coarse silicate autoclaved aggregate are the same substance.

[0033] The apparent density of each aggregate is shown in Table 1, and the gradation is shown in Figure 1 As shown, the fine autoclaved aggregate, coarse autoclaved aggregate and sintered ceramsite are all single-particle graded, and the particle sizes are 2.36-4.75mm, 4.75-9.5mm and 4.75-9.5mm respectively.

[0034] Table 1 Apparent density of each aggregate

[0035]

[0036] 1. Take C20 concrete as an example:

[0037] First, according to the current industry standard JGJ55 "Ordinary Concrete Mix Design Code" and through trial mixing, the preliminary mix ratio is obtained as follows:

[0038] Table 2C20 original mix ratio (kg / m 3 )

[0039] serial number cement Fly ash Slag powder water Machine-made sand gravel C20-0 171 69 35 176 1005 932

[0040] The slump of the fresh concrete mixture prepared according to Table 2 is 220mm, the side length is 150mm, the standard curing time of the cube test block is 28d, the compressive strength is 28MPa, and the wet density is 2379kg / m 3 .

[0041] Replace 25% of all aggregates with equal volume (fine aggregate uses fine autoclaved aggregate with a particle size of fine; coarse aggregate uses coarse autoclaved aggregate + sintered ceramsite, and the volume ratio of the two is 1:1; the overall coarse artificial aggregate volume: fine artificial aggregate volume = 1:2) and only replace crushed stone.

[0042] After the first adjustment (aggregate replacement) based on the preliminary mix ratio, the resulting mix ratio is:

[0043] Table 3C20 mix ratio after the first adjustment (kg / m 3 )

[0044]

[0045] The slump of the fresh concrete mixture prepared according to Table 3 is 240mm, the side length is 150mm, the standard curing time of the cube test block is 28d, the compressive strength is 29MPa, and the wet density is 2354kg / m 3 .

[0046] After the second adjustment (rubber material optimization), the resulting mix ratio is:

[0047] Table 4C20 mix ratio after the second optimization (kg / m 3 )

[0048]

[0049] The slump of the fresh concrete mixture prepared according to Table 4 is 220mm, the side length is 150mm, the standard curing 28d compressive strength is 28.5MPa, and the wet density is 2352kg / m 3 .

[0050] 2. Take C40 concrete as an example:

[0051] First, according to the current industry standard JGJ55 "Ordinary Concrete Mix Design Code" and through trial mixing, the preliminary mix ratio is obtained as follows:

[0052] Table 5C40 original mix ratio (kg / m 3 )

[0053] serial number cement Fly ash Slag powder water Machine-made sand gravel C40-0 280 80 40 180 785 1010

[0054] The slump of the fresh concrete mixture prepared according to Table 5 is 240mm, the side length is 150mm, the standard curing time of the cube test block is 28 days, the compressive strength is 50.1MPa, and the wet density is 2342kg / m 3 .

[0055] Replace 15% of all aggregates with equal volume (fine aggregate uses fine autoclaved aggregate with a particle size of fine; coarse aggregate uses coarse autoclaved aggregate + sintered ceramsite, and the volume ratio of the two is 1:1; the overall coarse artificial aggregate volume: fine artificial aggregate volume = 1:2) and only replace crushed stone.

[0056] After the first adjustment (aggregate replacement) based on the preliminary mix ratio, the resulting mix ratio is:

[0057] Table 6C40 mix ratio after the first adjustment (kg / m 3 )

[0058]

[0059]

[0060] The slump of the fresh concrete mixture prepared according to Table 3 is 265mm, the side length is 150mm, the standard curing time of the cube test block is 28 days, the compressive strength is 51.5MPa, and the wet density is 2344kg / m 3 .

[0061] After the second adjustment (rubber material optimization), the resulting mix ratio is:

[0062] Table 7C40 mix ratio after the second optimization (kg / m 3 )

[0063]

[0064] The slump of the fresh concrete mixture prepared according to Table 4 is 240mm, the side length is 150mm, the standard curing 28d compressive strength is 49MPa, and the wet density is 2368kg / m 3 .

[0065] 3. Take C60 concrete as an example:

[0066] First, according to the current industry standard JGJ55 "Ordinary Concrete Mix Design Code" and through trial mixing, the preliminary mix ratio is obtained as follows:

[0067] Table 8 Original mix ratio of C60 (kg / m 3 )

[0068] serial number cement Fly ash Slag powder water Machine-made sand gravel C60-0 350 100 50 160 700 1030

[0069] The slump of the fresh concrete mixture prepared according to Table 8 is 265mm, the side length is 150mm, the standard compressive strength of the cubic test block after 28d curing is 70.3MPa, and the wet density is 2375kg / m 3 .

[0070] Replace 10% of all aggregates with equal volume (fine aggregate uses fine autoclaved aggregate with a particle size of fine; coarse aggregate uses coarse autoclaved aggregate + sintered ceramsite, and the volume ratio of the two is 1:1; the overall coarse artificial aggregate volume: fine artificial aggregate volume = 1:2) and only replace crushed stone.

[0071] After the first adjustment (aggregate replacement) based on the preliminary mix ratio, the resulting mix ratio is:

[0072] Table 9C60 mix ratio after the first adjustment (kg / m 3 )

[0073]

[0074] The slump of the fresh concrete mixture prepared according to Table 9 is 290mm, the side length is 150mm, the standard compressive strength of the cubic test block after 28d curing is 75.6MPa, and the wet density is 2363kg / m 3 .

[0075] After the second adjustment (rubber material optimization), the resulting mix ratio is:

[0076] Table 10C60 mix ratio after the second optimization (kg / m 3 )

[0077]

[0078] The slump of the fresh concrete mixture prepared according to Table 10 is 260mm, the side length is 150mm, the standard curing 28d compressive strength is 69.5MPa, and the wet density is 2351kg / m 3 .

[0079] 4. Take C80 concrete as an example:

[0080] First, according to the current industry standard JGJ55 "Ordinary Concrete Mix Design Code" and through trial mixing, the preliminary mix ratio is obtained as follows:

[0081] Table 11C80 original mix ratio (kg / m 3 )

[0082] serial number cement Fly ash Slag powder water Machine-made sand gravel C80-0 423 121 60 154 629 997

[0083] The slump of the fresh concrete mixture prepared according to Table 11 is 275mm, the side length is 150mm, the standard curing 28d compressive strength is 94MPa, and the wet density is 2376kg / m 3 .

[0084] Replace 5% of all aggregates with equal volume (fine aggregate uses fine autoclaved aggregate with a particle size of fine; coarse aggregate uses coarse autoclaved aggregate + sintered ceramsite, and the volume ratio of the two is 1:1; the overall coarse artificial aggregate volume: fine artificial aggregate volume = 1:2) and only replace crushed stone.

[0085] After the first adjustment (aggregate replacement) based on the preliminary mix ratio, the resulting mix ratio is:

[0086] Table 12C80 mix ratio after the first adjustment (kg / m 3 )

[0087]

[0088] The slump of the fresh concrete mixture prepared according to Table 12 is 290mm, the side length is 150mm, the standard curing time of the cube test block is 28d, the compressive strength is 92MPa, and the wet density is 2376kg / m 3 .

[0089] After the second adjustment (rubber material optimization), the resulting mix ratio is:

[0090] Table 13C80 mix ratio after the second optimization (kg / m 3 )

[0091]

[0092] The slump of the fresh concrete mixture prepared according to Table 13 is 260mm, the side length is 150mm, the standard curing 28d compressive strength is 92MPa, and the wet density is 2369kg / m 3 .

Claims

1. A method for preparing low-carbon normal density structural concrete using artificial aggregate, characterized in that: On the basis of the conventional mix ratio of C20-C80 ordinary structural concrete, artificial coarse aggregate and fine aggregate accounting for 5%-25% of the total aggregate volume are added to reduce the cement dosage by 10-150kg / m 3 , water consumption is reduced by 5-50kg / m 3 , the insufficient volume can be supplemented with admixtures; The conventional mix ratio of C20-C80 ordinary structural concrete is 250kg / m 3 -700kg / m 3 In addition to ordinary Portland cement as a necessary component, the proportion of mineral admixtures does not exceed 50%. The water-binder ratio in the mix is ​​usually 0.25-0.55, and the amount of sand is 550kg / m 3 -950kg / m 3 The amount of crushed stone in the mix ratio is usually 900kg / m 3 -1200kg / m 3 ; The artificial coarse aggregate and fine aggregate have a particle size of 1.18mm-5mm for fine aggregate and 5mm-25mm for coarse aggregate, and an apparent density of 1700-2500kg / m 3 , the average cylinder pressure strength is not less than 8MPa, and the water absorption rate in 1 hour is 5-20%; The artificial coarse aggregate and fine aggregate are added in a proportion of 5% to 25% of the total volume of the aggregate. When the apparent density of the artificial aggregate is 1950 to 2500 kg / m 3 The maximum proportion of admixture is 25% of the total volume of aggregate. When the density of artificial aggregate is 1700~1950kg / m 3 Reach 15% of the total volume of aggregate; The volume ratio of artificial coarse aggregate to the total volume of artificial coarse and fine aggregates shall not exceed 50%; the artificial aggregate shall replace natural sand and gravel in equal volume.

2. The method according to claim 1, characterized in that: There are two ways to add artificial aggregate: 1) Pre-saturate with water for at least 24 hours in advance. When adding, remove the floating water on the surface of the aggregate and then add it to the mixer; 2) Add it to the mixer in a dry state, first add part or all of the additional water, and stir with the artificial aggregate for at least 20 seconds.

3. The method according to claim 1, characterized in that: The insufficient volume is supplemented by admixtures. After reducing the amount of cement and water, the concrete volume is less than 1 cubic meter, and the corresponding volume of fly ash should be added according to the insufficient volume.

Citation Information

Patent Citations

  • Lightweight high-strength concrete applicable to pumping construction and construction method

    CN106747098A

  • A synthetic fine aggregate silicate ceramic sand and its preparation method

    CN110078395B

  • Design method of mix proportion of LC50-LC80 light high-strength silicate ceramsite concrete

    CN110981333A

  • Light high-strength silicate ceramsite concrete

    CN111003991A

  • A lightweight high-strength concrete, its preparation method and application

    CN112266210B